Educational Attainment on the Production of Organic Fertilizer and Botanical Pesticides in Gumawang, Central Java, Indonesia: A Contribution to Sustainable Development Goals (SDGs) Number 2 - Widijanto, Hery; Marsal, Cristalina Jalil; Melati, Arum; Haq, Ghulam Zakiyya Thoriqul; Adzhani, Naufal Iman; Ningrum, Ni Kadek Sathya; Prayoga, Ridwan Priyo; Andjani, Salsabila; Pramesthy, Shafira Dwi; Lathifa, Marianna Nur (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2024)
The successful implementation of organic farming practices often hinges on factors beyond mere technological innovation, with socio-economic and educational variables playing crucial roles, especially in Gumawang, Central Java. This study aimed to provide insights into how educational interventions can contribute to achieving sustainable development goal (SDG) number 2 in rural communities in Gumawang, Central Java, Indonesia. The research investigates the relationship between education levels and the adoption of sustainable agriculture practices using a mixed-methods approach, which includes surveys, interviews, and observations. The results indicate a notable association between elevated educational attainment and the adoption of organic farming methodologies, encompassing the utilization of eco-friendly fertilizers and pesticides. Moreover, the research examines the significance of education in augmenting farmers’ understanding, competencies, and consciousness regarding sustainable agricultural methodologies, consequently making a valuable contribution to food security, environmental conservation, and rural advancement. The findings highlight the significance of educational interventions in promoting sustainable agriculture and furthering the sustainable SDGs, especially in rural communities such as Gumawang.